2021
DOI: 10.1021/acs.inorgchem.1c01212
|View full text |Cite
|
Sign up to set email alerts
|

Charge Localization and Magnetic Correlations in the Refined Structure of U3O7

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
(194 reference statements)
2
8
0
Order By: Relevance
“…The main phase is well refined using the U 3 O 7 model, but the lattice parameters obtained show only a weak tetragonal distortion, with axial ratio (c/a) strongly below the expected value of 1.032. 50 This weak tetragonal distortion is in agreement with previous observations and it is explained by the substoichiometry of the U 3 O 7Àz oxide. [51][52][53] This U 3 O 7Àz phase is the main phase of all four samples.…”
Section: Xrd Analysissupporting
confidence: 92%
“…The main phase is well refined using the U 3 O 7 model, but the lattice parameters obtained show only a weak tetragonal distortion, with axial ratio (c/a) strongly below the expected value of 1.032. 50 This weak tetragonal distortion is in agreement with previous observations and it is explained by the substoichiometry of the U 3 O 7Àz oxide. [51][52][53] This U 3 O 7Àz phase is the main phase of all four samples.…”
Section: Xrd Analysissupporting
confidence: 92%
“…The formula U 4 O 9 (or U 4 O 9– y ) is actually a simplification of the real structural formula U 256 O 572 (stoichiometry 2.234 instead of 2.25) that describes a superstructure in which excess oxygen defects are organized in cuboctahedral clusters, whose periodicity defines the superstructure itself. , The fluorite-related U 4 O 9 superstructure is characterized by a cubic cell ( I 4̅3 d ) with four-fold lattice dimensions with respect to the original UO 2(+ x ) ( a U 4 O 9 = 4 a UO 2+ x ). Further oxidation introduces more oxygen cuboctahedra and induces an anisotropic distortion in the structure, leading to the formation of tetragonal U 3 O 7 ( a / c > 1), in a similar way to what happens in other fluorite-related anion-excess superstructures such as Ca 2 YbO 7 …”
Section: Introductionmentioning
confidence: 79%
“…6−9 At high temperatures, UO 2 has a broad hyperstoichiometric domain (UO 2+x , with x increasing with temperature up to 0.24), where oxygen is included in the lattice and the cell gradually shrinks. 10,11 As the oxidation continues beyond the solubility limit of oxygen in UO 16 At temperatures around 200−300 °C, the first stage, with the formation of U 4 O 9 and U 3 O 7 , is characterized by a pseudoparabolic weight gain curve, typical of a diffusioncontrolled process. 17 The transformation of U 3 O 7 into orthorhombic U 3 O 8 is instead accompanied by a sigmoidal weight gain curve, related to a combination of a nucleation and growth mechanism 18 and macrocracking, 19 whose relative contribution is determined by factors such as temperature and sample characteristics (for example, the crystallite domain size).…”
Section: Introductionmentioning
confidence: 99%
“…The physico-chemical and structural properties of uranium and its oxide-derived compounds have been investigated extensively for almost a century (Grenthe et al, 2008), but new insights are still being reported on a regular basis (Soulie ´et al, 2019;Leinders et al, 2021;Miskowiec et al, 2021;Saniz et al, 2023;Prieur et al, 2021). Uranium finds its main application as a nuclear fuel in commercial power generation and research reactors.…”
Section: Introductionmentioning
confidence: 99%